Efektivitas Program Pengembangan Usaha Agribisnis Perdesaan (PUAP) Pada Peternakan Babi di Desa Macang Kabupaten Karangasem - Lestari, Ni Nyoman Santhi Pita; Utama, Made Suyana (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2017)
PUAP is a program which established by the ministry of agriculture, to tackle some challenges such as capital, marketing, and the under-qualified human resources that caused the low productivity of our farmers. The main reason of this research is to analyze how well the program (PUAP) works for the pigs’ farms at Macang Village in Karangasem regency, and to learn what factors that affecting the effectiveness of the program. This study took place at Macang Village, including some groups of farmers (Gapoktan) called Tunjung Mekar. There are 98 of researches that had been done, which is only half of the total farmers in the group of Tunjung Mekar. The research uses 2 methods in its study, first is descriptive analysis, to analyze the effectiveness of the program. And, second is confirmatory factor analysis, to confirm/ ensure the latent variables and its indicator. The result shows the effectiveness of this program is about 81,75 percent and categorized as effective. The most influential variable in the program are process, followed by output and last but not least the input.
Keywords: Effectivity, PUAP, Pig’s Farm